2020
DOI: 10.1111/jog.14314
|View full text |Cite
|
Sign up to set email alerts
|

Can preoperative inflammatory markers differentiate endometrial cancer from complex atypical hyperplasia/endometrial intraepithelial neoplasia?

Abstract: Aim: The aim of this study was to identify the differences between complex atypical hyperplasia/ endometrial intraepithelial neoplasia (CAH/EIN) and endometrioid-type grade 1 endometrial cancer in terms of preoperative systemic inflammatory markers and to evaluate the effectiveness of such markers in predicting cancer. Methods: Between January 2005 and September 2018, a total of 372 patients with final histopathologic diagnoses of CAH/EIN (n = 143) and endometrioid-type grade 1 endometrial cancer (n = 229) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…Pro-inflammatory cytokines (eg, IL1β, IL6, and IL8) may be predictive markers of the incidence and stage of cancer, as well as prognostic markers of DFS and OS. 115 Research on the use of anti-inflammatory drugs after surgery has been initiated to investigate the SIR-to-healing process following tumor resection. It has been shown that the use of such agents can improve treatment outcomes in patients with cancer and reduce the risk of disease recurrence after breast cancer surgery.…”
Section: The Role Of Chronic Inflammatory Reaction In Neoplastic Disease Relapsementioning
confidence: 99%
See 2 more Smart Citations
“…Pro-inflammatory cytokines (eg, IL1β, IL6, and IL8) may be predictive markers of the incidence and stage of cancer, as well as prognostic markers of DFS and OS. 115 Research on the use of anti-inflammatory drugs after surgery has been initiated to investigate the SIR-to-healing process following tumor resection. It has been shown that the use of such agents can improve treatment outcomes in patients with cancer and reduce the risk of disease recurrence after breast cancer surgery.…”
Section: The Role Of Chronic Inflammatory Reaction In Neoplastic Disease Relapsementioning
confidence: 99%
“… 114 Subsequently, Selen et al confirmed in a multivariate analysis that low PLR (≤133.3) was related to a statistically significant OR (8.01; p<0.001) for the diagnostic prediction of low-grade endometrioid endometrial cancer compared with endometrial intraepithelial neoplasia. 115 Acmaz et al investigated the diagnostic utility of elevated NLR and PLR in females experiencing abnormal bleeding. 116 Although the NLR was significantly higher in patients with cancer than in those with endometrial atypia and controls (p=0.001 and p=0.025, respectively), there was no difference between patients with simple endometrial hyperplasia and controls.…”
Section: Systemic Inflammatory Reaction In Neoplasms Of the Female Genital Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…В клинической практике наряду с традиционным подходом все большую распространенность получает применение классификации ВОЗ [1,2]. Идея разделения двух событий, эстрогенной стимуляции и мутационной активации, не только позволяет исследовать оба компонента по отдельности, но и дает более понятную модель многоэтапного канцерогенного процесса [1,3]. В качестве потенциальных биомаркеров для определения ГЭ, находящихся в зоне риска злокачественного перерождения, рассматриваются разнообразные иммуногистохимические и молекулярные факторы.…”
Section: экспериментальная медицинаunclassified
“…), гиперплазия эндометрия (ГЭ) делится на две группы: гиперплазия без атипии и гиперплазия с атипией (АГЭ)/эндометриальная интраэпителиальная неоплазия (ЭИН). Частота малигнизации для ГЭ без атипии составляет 1-3 %, в то время как для пациентов с АГЭ/ЭИН -30 % и более [2,3]. Такая тесная взаимосвязь и неуклонный рост встречаемости ГЭ и рака эндометрия, который является наиболее распространенным гинекологическим злокачественным новообразованием женщин в развитых странах в основном из-за старения населения и развития нарушений метаболизма, диктуют необходимость поиска эффективных диагностических и прогностических маркеров [4,5].…”
unclassified